Gαi2 is the essential Gαi protein in immune complex-induced lung disease - Wiege, Kristina; Ali, Syed R.; Gewecke, Britta; Novakovic, Ana; Konrad, Franziska M.; Pexa, Katja; Beer-Hammer, Sandra; Reutershan, Joerg; Piekorz, Roland P.; Schmidt, Reinhold E.; Nuernberg, Bernd; Gessner, J. Engelbert (Journal of Immunology, 2013)
Heterotrimeric G proteins of the Gαi family have been implicated in signaling pathways regulating cell migration in immune diseases. The Gαi-protein-coupled C5a receptor is a critical regulator of IgG FcR function in experimental models of immune complex (IC)-induced inflammation. By using mice deficient for Gαi2 or Gαi3, we show that Gαi2 is necessary for neutrophil influx in skin and lung Arthus reactions and agonist-induced neutrophilia in the peritoneum, whereas Gαi3 plays a less critical but variable role. Detailed analyses of the pulmonary IC-induced inflammatory response revealed several shared functions of Gαi2 and Gαi3, including mediating C5a anaphylatoxin receptor-induced activation of macrophages, involvement in alveolar production of chemokines, transition of neutrophils from bone marrow into blood, and modulation of CD11b and CD62L expression that account for neutrophil adhesion to endothelial cells. Interestingly, C5a-stimulated endothelial polymorphonuclear neutrophil transmigration, but not chemotaxis, is enhanced versus reduced in the absence of neutrophil Gαi3 or Gαi2, respectively, and knockdown of endothelial Gαi2 caused decreased transmigration of wild-type neutrophils. These data demonstrate that Gαi2 and Gαi3 contribute to inflammation by redundant, overlapping, and Gαi-isoform-specific mechanisms, with Gαi2 exhibiting unique functions in both neutrophils and endothelial cells that appear essential for polymorphonuclear neutrophil recruitment in IC disease. Copyright © 2012 by The American Association of Immunologists, Inc.
CRIS-Team Scopus Importer:2022-11-17